Fatal Hepatic Decompensation in a Patient with Hepatitis B Cirrhosis Following Famciclovir Withdrawal - Robert P Myers; Rabindra Chaudhary; Kevin Fonseca; Samuel S Lee (Canadian Journal of Gastroenterology)
Hepatitis B virus (HBV) infection is a major cause of chronic liver disease worldwide. Famciclovir is a nucleoside analogue with potent antiviral activity that appears promising in the management of patients with HBV infection. No data exist regarding the safety of nucleoside analogue withdrawal in patients treated for HBV cirrhosis. The authors describe a 41-year-old man with compensated HBV cirrhosis who developed fatal hepatic decompensation due to a rebound in viral replication within six weeks of discontinuing famciclovir therapy. Although several mutations in the HBV DNA polymerase gene have been documented, none has been associated with famciclovir resistance or adverse clinical outcomes. Clinicians should consider the risk of inducing serious flares in hepatic inflammation as a result of abrupt nucleoside analogue withdrawal. Until further data are available regarding the safety of withdrawal of these agents, indefinite treatment may be required in patients with established cirrhosis.